2013
DOI: 10.1159/000348424
|View full text |Cite
|
Sign up to set email alerts
|

Administration of <b><i>Bifidobacterium</i></b><b><i>animalis</i></b> subsp. <b><i>lactis</i></b> BB-12 in Early Childhood: A Post-Trial Effect on Caries Occurrence at Four Years of Age

Abstract: Probiotic bifidobacteria are widely used in the prevention of childhood diseases. These bacteria are also associated with caries occurrence. The present secondary analysis in a low-caries population evaluated the effect of early administration of Bifidobacterium animalis subsp. lactis BB-12 (BB-12) on caries occurrence and identified markers of dental decay in early childhood. In the original randomized, double-blind, placebo-controlled study (NCT00638677, http://www.clinicaltrials.gov), infants (n = 106) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 36 publications
1
48
3
5
Order By: Relevance
“…A similar inference was also reached by a qualitative systematic review of probiotic caries studies, concluding that clinical recommendations would be premature without more comprehensive RCTs showing an actual reduction in individual caries experience [Twetman and Keller, 2012]. Relatively few RCTs of oral probiotics have used clinical dental caries indicators to prove the efficacy of probiotics in preventing or treating dental caries [Näse et al, 2001;Stecksén-Blicks et al, 2009;Burton et al, 2013;Taipale et al, 2013]. A comprehensive systematic review utilizing evidence from these RCTs concluded that current evidence is insufficient for recommending probiotics in controlling dental caries [Gruner et al, 2016].…”
Section: Probioticsmentioning
confidence: 75%
“…A similar inference was also reached by a qualitative systematic review of probiotic caries studies, concluding that clinical recommendations would be premature without more comprehensive RCTs showing an actual reduction in individual caries experience [Twetman and Keller, 2012]. Relatively few RCTs of oral probiotics have used clinical dental caries indicators to prove the efficacy of probiotics in preventing or treating dental caries [Näse et al, 2001;Stecksén-Blicks et al, 2009;Burton et al, 2013;Taipale et al, 2013]. A comprehensive systematic review utilizing evidence from these RCTs concluded that current evidence is insufficient for recommending probiotics in controlling dental caries [Gruner et al, 2016].…”
Section: Probioticsmentioning
confidence: 75%
“…In a study in adults with established root caries, Petersson et al [2011] found partial reversal of the lesions after daily intake, for 15 months, of milk supplemented with probiotic bacteria. In contrast, the study by Taipale et al [2013] found no difference in caries prevalence in 4-year-old children who during the first year of life had been treated with probiotic bacteria, compared to those who received xylitol or sorbitol administered in the same way. Neither, Hasslöf et al [2013] found any effect on caries at 9 years of age after supplementation of L. paracasei (LF19) in cereals for the first 4-13 months of life.…”
mentioning
confidence: 83%
“…Several studies have shown positive effects of probiotic lactobacilli: reduction in the number of mutans streptococci, dental plaque and gingival inflammation [Nikawa et al, 2004;Krasse et al, 2006;Calgar et al, 2008;Marttinen et al, 2012]. To date, however, only five studies have been published with caries as the endpoint [Näse et al, 2002;Stecksén-Blicks et al, 2009;Petersson et al, 2011;Hasslöf et al, 2013;Taipale et al, 2013], three of which report lower caries increment after exposure to probiotic bacteria compared to control groups. In the study by Näse et al [2002], preschool children were exposed to milk with L. rhamnosus five days a week over seven months at 1-6 years of age.…”
mentioning
confidence: 99%
“…Finally, we modeled a repetitive uptake of probiotics. In a clinical setting, this was deemed necessary given the poor retention of certain probiotic strains [Taipale et al, 2012[Taipale et al, , 2013 but might decrease the possible efficacy of any probiotic therapy, as it requires patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, both in vitro and clinical studies yielded ambiguous results with regard to the benefits or risks associated with caries prevention via probiotics. While a number of studies reported reduced numbers of cariogenic bacteria after probiotic therapy [Laleman et al, 2014;Gruner et al, 2016], others did not confirm such effects Marttinen et al, 2012;Taipale et al, 2012Taipale et al, , 2013. Furthermore, the beneficial effects of probiotics on carious lesions have been reported [Näse et al, 2001], but not always confirmed Hasslöf et al, 2013].…”
mentioning
confidence: 99%